The Effect of Multiple Intelligence-Based Instruction on Critical Thinking of Full Day Islamic Elementary Schools Students - Alhamuddin Alhamuddin; Bukhori Bukhori (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2016)
Lack of critical thinking skills of elementary schools’ students was influenced by teachers’ domination in instructional activities; meanwhile students did not play independently as the learners. Theoretically, multiple intelligences based instruction is an appropriate solution. For that reason, this research aims to know the impact of multiple intelligences based instruction on students' critical thinking skills. The research was conducted at Al-Amanah and Buahati Islamic Elementary Schools by using a quantitative approach with case study method. Data collected through critical thinking tests was analyzed by using independent sample t-test to examine the impact of instruction on students' critical thinking skills. The results showed that the implementation of multiple intelligences based intruction had significant effect on students’ critical thinking skills. From the finding, some recommendations are given as follows: 1) The teacher’s role is not only for transferring knowledge based on his/her competencies but also students’ characteristics reflecting their instruction styles; and 2) for further researcher, it is suggested to investigate this issues more specifically and comprehensively. Kurangnya keterampilan berpikir kritis dari siswa sekolah dasar dipengaruhi oleh dominasi guru dalam kegiatan pembelajaran; Sementara itu siswa tidak bermain secara independen sebagai peserta didik. Secara teoritis, pendekatan berbasis kecerdasan ganda merupakan solusi yang tepat. Untuk itu, penelitian ini bertujuan untuk mengetahui dampak pendekatan berbasis kecerdasan ganda pada keterampilan berpikir kritis siswa. Penelitian ini dilakukan di Sekolah Dasar Islam Al-Amanah dan Buahati dengan menggunakan pendekatan kuantitatif dengan metode studi kasus. Data dikumpulkan melalui tes berpikir kritis dianalisis dengan menggunakan sampel independent t-test untuk menguji dampak dari pendekatan pada keterampilan berpikir kritis siswa. Hasil penelitian menunjukkan bahwa pelaksanaan pendekatan berbasis kecerdasan ganda memiliki dampak yang signifikan terhadap kemampuan berpikir kritis siswa. Dari temuan tersebut, beberapa rekomendasi yang diberikan sebagai berikut: 1) Peran guru tidak hanya untuk mentransfer pengetahuan berdasarkan kompetensinya, tapi juga karakteristik siswa mencerminkan gaya pendekatan mereka; dan 2) bagi peneliti selanjutnya, disarankan untuk menyelidiki ini secara lebih spesifik dan komprehensif.